Ecological aspects of studying the thyroid function of the thyroid gland in women of reproductive age living in a region with iodine deficiency (Akhtynsky district, Republic of Dagestan, Russia) - A. N. Dzhalilova; S. M. Omarova; D. N. Dzhalilova; T. V. Tsarueva; N. K. Abuduev; G. M. Gaziev; M. T. Yusupova; P. S. Saidova; U. A. Magomedova (Юг России: экология, развитие)
Aim. To present epidemiological aspects of the study of thyroid function of the thyroid gland.The article presents the results of a clinical and laboratory examination and epidemiological aspects of studying the thyroid function of the thyroid gland in 120 women of reproductive age living in an area with iodine deficiency (Akhtynsky district, Republic of Dagestan – located at an altitude of 1.675 metres above sea level). The women were examined for thyroid diseases and for the presence of intrauterine infections: TORCH toxoplasmosis, ornithosis, rubella, cytomegalo‐ and herpesviruses.All the examined patients had thyroid diseases (the women are registered with an endocrinologist at an Endocrinological Dispensary). All women underwent correction of iodine deficiency in the form of iodine prophylaxis by taking medications containing a daily iodine requirement of up to 250 mcg to normalize thyroid function.Intrauterine infections (IUI) were found in 76 women (69 %. of the patients examined). Intrauterine infections of women registered in the women's clinic of the district hospital were also treated.